PEMBATASAN PEMILIKAN DAN PENGUASAAN HAK ATAS TANAH DALAM PERSPEKTIF REFORMA AGRARIA - Reki, Natanael Dwi (Jurnal Hukum Magnum Opus, 2018)
The urgency of proprietary restriction and domination over the land more emphasized on the societyâ€™s interests at large. This view rely on philosophy of Pancasila related to the social justice meaning for whole Indonesia citizen. Then this restriction implementation intended State endowed a justice for land owner particularly the investors. State warrant the restriction by over takingÂ Â  and revoke land title right and either individually or business entity whenever it against the general accepted. It remind the spirit of Article 33 paragraph (3) said : â€œearth and water and the richness contained inside them powered by State and utilized as much as possible for the peopleâ€™s prosperityâ€. This provision confirmed by restriction guarantee through Article 7, 8, 9 and 10 which relevance with land domination restriction. Therefore in this case it is necessary to be organized and improvement in land restriction implementation systematically connected with agraria reform. Government enact the policies over attribution authority by laws to perform the restriction on domination and land proprietary for the sake of justice for whole Indonesia citizen. These authority can be run through concrete methods that is doing an action take over and revoke the land title permit as regulated Article 18 UUPA (Agraria Law).Keywords: land proprietary, land domination, restriction guarantee, article 33 paragraph (3)